Ablation of androgen receptor gene triggers right ventricular outflow tract ventricular tachycardia. (15th June 2015) - Tsai, Wen-Chin; Lu, Yen-Yu; Chen, Yao-Chang; Chang, Chien-Jung; Kao, Yu-Hsun; Lin, Yung-Kuo; Chen, Yu-Hsin; Chen, Shih-Ann; Yang, Liang-Yo; Chen, Yi-Jen
Abstract: Background: Sex hormones and calcium (Ca 2 + ) regulation play roles in the pathophysiology of ventricular tachycardia from right ventricular outflow tract (RVOT). The purpose of this study was to evaluate whether androgen receptor knockout (ARKO) can increase RVOT arrhythmogenesis through modulating RVOT electrophysiology and Ca 2 + homeostasis. Methods: Conventional microelectrodes were used to study the action potential (AP) in RVOT tissues prepared from wild type (WT) and ARKO mice (aged 6–10 months) before and after caffeine (1 mM), isoproterenol (1 μM), adenosine (10 μM) and flecainide (5 μM) administration. The Fluo-3 fluorescence Ca 2 + imaging with confocal microscopy and western blots were used to investigate intracellular Ca 2 + (Ca 2 + i ) transients, Ca 2 + sparks, and the expressions of ionic channel proteins in ARKO and WT RVOT myocytes. Results: We found that ARKO RVOTs ( n  = 13) had longer AP duration, faster burst firing (5.4 ± 0.7 vs. 3.4 ± 0.7 Hz, P < 0.05), and higher incidence of early afterdepolarizations (82% vs. 8%, P < 0.001) than WT RVOTs ( n  = 11). Adenosine and flecainide can suppress caffeine- or isoproterenol-induced spontaneous rates and burst firing in WT RVOTs, but not in ARKO RVOTs. ARKO RVOT myocytes had a higher frequency (7.7 ± 2.8 vs. 1.3 ± 0.4 spark/mm/s, P < 0.05) and incidence (89% vs. 47%, P < 0.05) of Ca 2 + sparks, and greater expressions of Cav1.2, NCX, phosphorylated RyR (s2814), phosphorylated phospholamban (Thr17), CAMKII and GRK2 than WT RVOT myocytes. However, ARKO and WT RVOT myocytes exhibit similar Ca 2 + i transients and SR Ca 2 + content, and less expression of calsequestrin. Conclusions: ARKO changes RVOT electrophysiology and Ca 2 + homeostasis with increased ventricular arrhythmogenesis.